Aligning mission preferences: Does self-selection foster performance in working groups? - Caroline Baethge; Marina Fiedler (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2016)
The following study investigates whether or not self-selection into organizations fosters performance in working groups by aligning mission preferences. The experimental design that allows us to study the causal relationship between self-selection, incentives and performance is based on a weak-link game devised by van Huyck et al. (1990). This is the optimal tool to illustrate the coordination and motivation problem within both public and private firms because it resembles the effort and performance process within working groups. The literature on the sorting effect of incentives focuses almost exclusively on the choice of certain compensation schemes. However, several studies on work attitudes indicate that employees not only differ concerning their preference for extrinsic or intrinsic rewards, but that other factors such as the organizational context also have an impact on the matching of employees and organizations and therefore the effectiveness of incentives. The interesting question now is whether or not selfselection does indeed align mission preferences and is the key to an employee's performance. We propose that neither the performance in working groups nor the effectiveness of a financial incentive are directly affected by self-selection but crucially depend on congruent values between employees and organizations.
Keywords: 650; self-selection; mission preferences; effectiveness of financial incentives; experiment